Dairy Consumption, Lactase Persistence, and Mortality Risk in a Cohort From Southern Sweden - Sonestedt, Emily; Borné, Yan; Wirfält, Elisabet; Ericson, Ulrika (Frontiers in Nutrition, 2021)
Background: Whether high dairy consumption is related to longevity is still unclear, and additional studies of prospective cohorts with high-quality dietary data from populations with wide consumption ranges are needed. Objective: To examine the association between dairy consumption and mortality in a Swedish cohort. Design: Among 26,190 participants (62% females, 45-73 years old) without diabetes and cardiovascular disease from the population-based Malmö Diet and Cancer cohort, 7156 individuals died during a mean follow-up time of 19 years. Data on intake of dairy (non-fermented milk, fermented milk, cheese, cream and butter) were collected from 7-day food records and food questionnaires. A genetic marker (rs4988235) associated with lactase persistence was detected among 22,234 individuals born in Sweden. Results: Higher intakes up to 1000 g/day of non-fermented milk were associated with only marginal higher mortality rates after adjusting for potential confounders. However, intakes above 1000 g/day (1.5% of the population) were associated with 34% (95% CI: 14, 59%, p-trend=0.002) higher mortality compared to that with less than 200 g/day. Fermented milk and cheese intake were inversely associated with mortality. Cream showed a protective association only among men. Butter was not associated with mortality. CT/TT genotype carriers (i.e., individuals with lactase persistence) had a 27% higher reported consumption of non-fermented milk, and non-significant higher mortality risk (HR=1.08; 95% CI=0.96, 1.23; p=0.20) than CC genotype carriers. Conclusions: Higher mortality rates were mainly observed among participants consuming more than 1000 g of non-fermented milk per day. In contrast, fermented milk and cheese were associated with lower mortality. Because dairy products differ in composition, it is important to examine them separately in their relation to health and disease. The use of a genetic variant as an objective marker of lactose-containing milk intake should be examined in relation to mortality in a larger population.